Comparing multistate expected damages, option price and cumulative prospect measures for valuing flood protection. Issue 5 (28th May 2013) - Farrow, Scott; Scott, Michael
Key Points The key choice is between non‐expected and expected utility measures. Continuous event modeling is useful The basic non‐expected utility value is less than the expected utility value